(untitled) (Bangladesh Journal of Medical Science, 2012)
Design: The study was a community based cross sectional study. Objective: The study was conducted to find out the reproductive health profile of rural married women of a selected rural community in Dhamrai Upazila of Dhaka district. Materials and Methods: The study was conducted among 204 married women of reproductive age included considering specific selection criteria. Data were collected by face-to-face interview using a semi-structured questionnaire. Maintaining quality control check data were processed and analyzed by using SPSS software. Results: The study revealed that majority of the women were either illiterate (34.1%) or had primary education (33.3%) with mean age of 31+8.65 years. Most of them (88.2%) were house wives and major segment (52.9%) had poor monthly family income (Tk.5000-10000). Among all, 63.7% were married within 11-17 years of age and 69.8% gave birth of first child during adolescence (16- 18 years). Major part (60.29%) of the women didn’t use any contraceptive and only 38.55% utilized antenatal care. Average number of children was 2.73+1.52 and most of the delivery (81.6%) was conducted at home by untrained birth attendants (57.0%). Adverse pregnancy outcome included abortion, menstruation regulation, still birth, complications to new born and mothers. Reproductive health problems faced by the women included menstrual problem, physical assault, leucorrhea, mental torment, sexual annoyance, puerperal infection, pregnancy related complications, urinary tract infection & pelvic inflammatory disease. Most (81.43%) of the illiterate women didn’t utilize ante-natal care while majority (60.0%) having higher secondary school certificate (HSC) had =3 ante-natal visits and this variation was statistically significant [?2(12)=26.35, p<0.05]. Majority (71.21%) of the illiterate women didn’t use any contraceptive method while most of them having HSC used either condom or oral contraceptive and this discrepancy was statistically significant [?2(12)=27.86, p<0.05]. Majority (67.1%) of the illiterate women were delivered by untrained birth attendants whereas all women having HSC were delivered by doctor (40.0%), nurse (20.0%) and traditional birth attendant (40.0%), this difference was statistically significant [?2(12)=24.57, p<0.05]. Conclusion: Reproductive health profile was worse among the illiterate, less aware and low income rural women. The study recommends formulation and implementation of effective strategies to improve reproductive health status of the rural women. Key words: Married women; reproductive health; pregnancy profile; rural community. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9496 BJMS 2011; 10 (4): 252-256